2015
DOI: 10.1038/srep11454
|View full text |Cite
|
Sign up to set email alerts
|

Cortical actin networks induce spatio-temporal confinement of phospholipids in the plasma membrane – a minimally invasive investigation by STED-FCS

Abstract: Important discoveries in the last decades have changed our view of the plasma membrane organisation. Specifically, the cortical cytoskeleton has emerged as a key modulator of the lateral diffusion of membrane proteins. Cytoskeleton-dependent compartmentalised lipid diffusion has been proposed, but this concept remains controversial because this phenomenon has thus far only been observed with artefact-prone probes in combination with a single technique: single particle tracking. In this paper, we report the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
131
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 43 publications
11
131
1
Order By: Relevance
“…In comparison, identically labeled phosphatidylethanolamine appeared to diffuse freely in the membrane (Eggeling et al, 2009), which implied that lipid-cytoskeleton interactions were not responsible for the anomalous cholesterol-dependent sphingolipid diffusion. Noteworthy, this finding of unhindered phosphatidylethanolamine diffusion conflicts with a previous single molecule tracking study (Fujiwara et al, 2002), and subsequent STED-FCS and single molecule tracking studies reported by these authors and others (Andrade et al, 2015; Fujiwara et al, 2016; Komura et al, 2016). Although, the authors of the STED study never concluded that the cholesterol-dependent trapping of sphingomyelin, GM1 and GPI-anchored proteins was indicative of tiny lipid rafts, their results were often cited by others as support for the lipid raft hypothesis (Lingwood and Simons, 2010; Levental and Veatch, 2016).…”
Section: Super-resolution Fluorescence Imaging Of Fluorescent Sphingocontrasting
confidence: 88%
See 1 more Smart Citation
“…In comparison, identically labeled phosphatidylethanolamine appeared to diffuse freely in the membrane (Eggeling et al, 2009), which implied that lipid-cytoskeleton interactions were not responsible for the anomalous cholesterol-dependent sphingolipid diffusion. Noteworthy, this finding of unhindered phosphatidylethanolamine diffusion conflicts with a previous single molecule tracking study (Fujiwara et al, 2002), and subsequent STED-FCS and single molecule tracking studies reported by these authors and others (Andrade et al, 2015; Fujiwara et al, 2016; Komura et al, 2016). Although, the authors of the STED study never concluded that the cholesterol-dependent trapping of sphingomyelin, GM1 and GPI-anchored proteins was indicative of tiny lipid rafts, their results were often cited by others as support for the lipid raft hypothesis (Lingwood and Simons, 2010; Levental and Veatch, 2016).…”
Section: Super-resolution Fluorescence Imaging Of Fluorescent Sphingocontrasting
confidence: 88%
“…Perhaps the most influential super-resolution imaging studies of membrane organization revealed complex lipid dynamics that were ultimately inconsistent with partitioning into liquid-ordered membrane domains produced by favorable cholesterol-and sphingolipid interactions (Hiramoto-Yamaki et al, 2014; Honigmann et al, 2014; Andrade et al, 2015; Sevcsik et al, 2015). Stimulated emission depletion (STED) fluorescence microscopy imaging demonstrated fluorophore-labeled sphingomyelin, GM1, and a GPI-anchored protein were temporarily trapped within 20-nm-diameter areas in the plasma membrane of living cells, and this trapping was cholesterol-dependent (Eggeling et al, 2009).…”
Section: Super-resolution Fluorescence Imaging Of Fluorescent Sphingomentioning
confidence: 99%
“…5, F-I). A positive feature of STED is that, being a confocal microscopy-based technology, it can be used for superresolution in combination with quantitative imaging methods such as fluorescence correlation spectroscopy (FCS) either at the cell surface (Andrade et al, 2015) or in deeper parts of the cell (Lanzanò et al, 2017). Unlike SIM and PALM/STORM, which require postacquisition image processing to deliver the superresolved result, STED provides superresolution during acquisition.…”
Section: Stedmentioning
confidence: 99%
“…A recent study suggested that not only proteins but also phospholipids are confined by the cortical actin network (Andrade et al, 2015). They used STED-FCS to monitor lipid probes in the plasma membrane and found that cortical actin networks induce spatiotemporal confinement of phospholipids on the plasma membrane.…”
Section: Cytoskeleton-dependent Compartmentalised Lipid Diffusionmentioning
confidence: 99%